Risk Factors of Postoperative Pneumonia after Coronary Artery Bypass Graft: A Scoping Review - Kumalasari, Regina Indah; Kosasih, Cecep Eli; Prawesti, Ayu (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Postoperative pneumonia (POP) is the most common complication in patients after CABG surgery. It increases morbidity, mortality, length of stay, and hospitalization costs. This review aims to identify the factors that influence pneumonia and the microorganisms that cause it in CABG postoperative patients. This scoping review used the framework developed by Arksey and O'Malley (2005). Primary sources of information were searched through five databases: PubMed, Scopus, Science Direct, Oxford, and EBSCO, and 2 search engines: Sage and Google Scholar. Article quality was assessed using the Joanna Briggs Institute critical appraisal checklist. A total of 8 articles with a total of 35235 participants were included in this review. The prevalence of post-CABG POP ranged from 2.4% to 18%. Dominant factors influencing postoperative pneumonia included duration of surgery, CPB time, blood transfusion, mechanical ventilation, LVAD/Tx, smoking history, chronic lung disease, and preoperative malnutrition. Meanwhile, the microorganisms that cause postoperative pneumonia are gram-positive and negative bacteria, fungi, and other bacteria. Infection prevention can be an important point in the CABG postoperative care continuum. By understanding the factors that influence POP, healthcare professionals can optimize patient outcomes, reduce complications, and improve the efficiency of postoperative care.